NEWS DISCOURSE IN SIMULTANEOUS INTERPRETATION: COGNITIVE AND PRAGMATIC CHALLENGES - Khayriniso Tukhtasinova (International Journal of Literature and Language Studies, 2026)
This article offers an in-depth analysis of the cognitive and pragmatic challenges encountered in the simultaneous interpretation of news discourse. It examines the psychological and linguistic difficulties interpreters face when processing news texts in real time. Drawing on theoretical foundations, classical and contemporary approaches, regional and national research, and practical examples, the article elucidates the core issues inherent in this field. The study concludes with scientific insights and proposed solutions to address these challenges.